Activities of Fedor Sannikov as a Supervisor of Schools in Ekaterinburg (1747—1751) - A. M. Safronova (Научный диалог)
This article examines, for the first time, the activities of Fedor Sannikov as the superintendent of Yekaterinburg schools, based on archival documents. It is noted that he had to fulfill his duties in a difficult environment, as tensions arose between him and the administration. As a result, his proposals were likely intentionally delayed or rejected. Despite the unfavorable attitude and even resistance from his superiors, Sannikov made every effort to modernize the schools. In particular, he insisted on reintroducing parallel vocational training for students, as introduced by V. N. Tatishchev according to a document from 1736. Sannikov repeatedly made proposals to increase the number of teachers in the arithmetic school, where he taught over 100 students. It has been established that under the supervision of the superintendent, there were more than 270-280 students in Yekaterinburg schools by the mid-18th century, and Sannikov was aware of the financial situation, abilities, and academic achievements of each of them. In the conditions of rising costs in the late 1740s, he proposed training students in crafts and allowing them to work in workshops in the second half of the day, as the students’ government stipend was not enough for clothing, shoes, food, and many had to rely on charity. Sannikov also paid attention to the education of noble children whose parents were not inclined to send them to schools.